Avaliação da proteção da fertilidade e da reserva ovariana com o uso deantagonistas do GnRH em ratas submetidas à quimioterapia comciclofosfamida - Claudia Navarro Carvalho Duarte Lemos (2008)
Improvements in the success of cancer treatments have resulted in a significant increase in life expectancy. However, these therapies can have some undesirable consequences, as the lost of gonadal function what can result in Premature Ovarian Failure. It has been shown that pre-puberty patients are more resistant to this lost, suggesting thatthe chemotherapies act mainly in the growing gonadal cells. The purpose of this study was to demonstrate that the maintenance of these cells in rest state with the use of antagonists of GnRH, would promote an adequate ovarian protection, and consequently preserve the fertility. It was a prospective study with Wistar rats divided into four groups: Group I: ninerats that received injection of placebo (P) plus placebo (P + P); group II: twelve rats that received injection of placebo (P) + cyclophosphamide (CFA) to evaluate effects of the CFA in the fertility and the ovarian function (P + CFA); group III: twelve rats that received injection of GnRH antagonist cetrorelix + CFA to evaluate the protective effect of the antagonist GnRH in the fertility and in ovarian function of the rats submitted to CFA(GnRHant + CFA); group IV: nine rats that received injection of GnRH antagonist (GnRHant) - cetrorelix to evaluate the effect of the GnRHant in the fertility and in ovarian function (GnRHant + P). After the use of the medications, the estral cycle was studied. The rats were matched, and the number of baby rats was evaluated in each group. After thebirth, the rats were sacrificed and the ovaries were prepared for histological study. The area of the axial cut was calculated in each ovary and the number of follicles was counted. All of them, apart from one rat of Group II (P + CFA), presented regular estral cycle. The statistics analysis showed that the group that received GnRHant previously to the CFA(GnRHant + CFA) had a significantly bigger number of baby rats (7 +/-1,31) than the group that received only CFA (p<0,05), but still less than the control group (p>0,05). The group that received only GnRHant did not differ from controls one. In relation to the ovarian cut area, these values did not present statistical difference. The analysis of the number of follicles did not find difference statistic, when each type of follicle wasevaluated separately, but the group treated only with GnRHant (GnRHant + P) presented a bigger number than the control group (17, 11 +/- 22), what was statistically significant (p<0,05). This data suggests that the use of the GnRHant: cetrorelix, before the chemotherapy with cyclophosphamide, can present a fertility protection